2014
DOI: 10.1589/jpts.26.1445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Indoor Horseback Riding Exercise on Electromyographic Activity and Balance in One-leg Standing

Abstract: [Purpose] This study investigated the influence of the indoor horseback riding exercise on the electromyographic activity of the lower extremity and balance during one-leg standing. [Subjects] Twenty normal adults were divided into an indoor horseback riding exercise group (IHREG, n=10), which performed the indoor horseback riding exercise using equipment 3 times a week for 3 weeks, and a control group (CG, n=10), which performed no exercise. [Methods] For comparitive analysis, an electromyographic test was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Horseback riding training requires longer time intervals of aerobic muscle strain, whereby this activity, initiated by the requirements of the training itself, can be responsible for the improvement of aerobic repetitive strength among riders (Westerling, 1983). The authors Lee et al (2014), Eisersiö et al (2015), Elmeua et al (2020), and Kuyulu, et al (2023 all report that horseback riding improves overall muscle strength of the arms (m. biceps brachii, m. triceps brachii), trunk (m. rectus abdominis, m. transversus abdominis, m. obliques abdominis, m. gluteus maximus, m. latissimus dorsi), and legs (m. adductor longus, m. quadriceps femoris), which supports the findings of this study. The results indicate a statistically significant difference in repetitive strength (Table 4.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horseback riding training requires longer time intervals of aerobic muscle strain, whereby this activity, initiated by the requirements of the training itself, can be responsible for the improvement of aerobic repetitive strength among riders (Westerling, 1983). The authors Lee et al (2014), Eisersiö et al (2015), Elmeua et al (2020), and Kuyulu, et al (2023 all report that horseback riding improves overall muscle strength of the arms (m. biceps brachii, m. triceps brachii), trunk (m. rectus abdominis, m. transversus abdominis, m. obliques abdominis, m. gluteus maximus, m. latissimus dorsi), and legs (m. adductor longus, m. quadriceps femoris), which supports the findings of this study. The results indicate a statistically significant difference in repetitive strength (Table 4.).…”
Section: Discussionmentioning
confidence: 99%
“…Liptak (2005) points out that riding improves muscle strength, agility, balance, and coordination. The results of the study by Lee et al (2014) suggest that horse riding simulation in women has a positive effect on the development of balance, flexibility, lower extremities muscle strength, and muscle endurance. The findings of a study by Kuyulu & Kara (2023) show that riding affects the development of balance and improves limb muscle strength.…”
Section: Introductionmentioning
confidence: 95%
“…Back and Kim 7 ) conducted a study on horseback riding simulation training for eight weeks with stroke patients and reported improvements in balance capabilities as well as the thickness of abdominal muscles. Lee et al 8 ) reported that indoor horseback riding exercise significantly improved muscle activities in the rectus femoris and adductor longus in normal adults. Back et al 2 ) reported that exercises performed by 40 normal adults using a horseback riding simulator increased muscle activity in the biceps brachii, transverse abdominis, abdominal oblique, and adductor longus muscles compared with jogging.…”
Section: Discussionmentioning
confidence: 99%
“…Riding is an aerobic exercise because horse riders have the similar respiratory capacity compared to soccer player. Lee et al (2014) reported that indoor horse riding apparatus improves women’s muscle strength, muscle endurance, balance, flexibility and remarkably femur muscle strength and its endurance ( Lee et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%